Is CSR Assistance Effective for Islamic Based Community Development in Indonesia? - Hadi, Nor; Baihaqi, Jadzil (Ekonomi Syariah IAIN Kudus, 2020)
This article strives to examine which CSR assistance factors are effective in helping to alleviate the burdens of a community who lives near a cement site. The CSR factors are developed from underlying intens of Islamic law (maqasid al-sharia). The CSR activities which are done by the company towards the community residing near the site are in the form of community development and partnerships. This study was conducted in a community residing around a mine. Primary data were utilized. The data were retrieved with a survey technique, and 97 respondents were retrieved. Meanwhile, the data were analyzed by using a factor analysis. The analysis results depict that there are 6 kinds of education assistance in the CSR programs, where assistance in establishing free schools is not effective enough because it is used for employees’ children, while they comprise a very small portion of the community. There are 20 CSR health programs for the community, while the only one that is not very effective is the HIV prevention program, because the company does not implement an HIV prevention program for the community. There are 12 CSR programs for the environment, in which all of the programs are considered to be effective for the community. There are 6 CSR socio-religious programs, while only 2 of them are considered as not being effective, which are the holiday and animal sacrifice assistance. There are 4 CSR programs for public infrastructure, in which all of the programs are effective to alleviate the community’s burdens. There are 2 CSR programs for national holidays, in which all of the programs are effective for the community. There are 5 socio-cultural CSR programs, in which 2 of the CSR programs are considered to not be effective, which are the arts and culture mentoring as well as arts and culture festival assistance. There are 7 CSR programs for youth and sports activities, which are all considered effective for the community. There are 4 other CSR programs for social assistance, in which 2 of the programs are viewed as being ineffective, which are the retirement home and death assistance. There are 4 CSR programs for rotating fund assistance for SMEs, which are all deemed effective for the community. There are 3 CSR programs for managerial assistance for SMEs, in which 1 program is thought to be ineffective, which is the record keeping and accounting training program. There are 3 CSR programs for marketing assistance for SMEs, which are all considered effective for SMEs.